A. I. KUKHTENKO IN THE AREA OF INERTIAL NAVIGATION AND INERTIAL CONTROL SYSTEMS - Lebedev, D. V.; Tkachenko, A. I. (Problems of Informatization and Management, 2021)
An important area of research carried out at the Institute of Cybernetics of the Academy of Sciences of Ukraine under the leadership of A. I. Kukhtenko, there were works in the field of inertial navigation and inertial control systems.